A Self‐Powered ZnO‐Nanorod/CuSCN UV Photodetector Exhibiting Rapid Response. (7th December 2012) - Hatch, Sabina M.; Briscoe, Joe; Dunn, Steve
<x xml:space="preserve">Abstract</x> The pre‐existing Fermi level alignment between ZnO and CuSCN semiconductors gives rise to the two key elements needed for a self‐powered, binary‐response UV‐ sensor: photovoltaic behavior and low turn‐on bias. Nanosecond response times, self‐powered performance, and long‐term stability, coupled with scalable, inexpensive fabrication on the nanoscale, offer currently unmatched progression towards self‐sufficient nanoscale systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>